Investigation of Lipid Oxidation in High‐ and Low‐Lipid‐Containing Topical Skin Formulations. (22nd August 2017) - Thomsen, B. R.; Horn, A. F.; Hyldig, G.; Taylor, R.; Blenkiron, P.; Jacobsen, C.
Abstract: Lipid oxidation can impact the odour of skin care products during storage. A study was conducted to identify and monitor representative markers for lipid oxidation in skin care products over time. Four lip care formulations and three skin care formulations with different lipid contents were stored at various cosmetic industry‐relevant conditions for 84 days. The skin care products were analysed for lipid hydroperoxides and secondary volatile oxidation products. A trained sensory panel performed an odour difference (triangle) test and odour‐profiled the products to detect and describe odour changes during storage. Several potential markers for lipid oxidation were identified. In skin care formulations, peroxide value (PV) analysis was a useful marker for lipid oxidation if the product was exposed to light during storage, but no clear changes were observed for PV in samples stored under other conditions. Furthermore, concentrations of several secondary volatile oxidation products increased during storage, and the highest increase was observed for products exposed to light. Pentanal and heptanal were found to be reliable markers for secondary volatile oxidation products in the skin care formulations (especially during exposure to light), whereas in the lip care formulations the best candidates were pentanal (especially during exposure to light and iron), 2‐methyl furan and 3‐methyl‐3‐buten‐2‐one (especially during exposure to light, iron and high temperatures). Graphical Abstract: